POTENSI CADANGAN KARBON TEGAKAN HUTAN SUB MONTANA DI TAMAN NASIONAL GUNUNG HALIMUN SALAK - Virni Budi Arifanti; I Wayan Susi Dharmawan; Donny Wicaksono (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2014)
Several baseline data of natural forest carbon stock is needed to support REDD+ (Reducing Emission from Deforestation and Degradation+) implementation as a mitigation effort for climate change issue in Indonesia. According to IPCC (Intergovernmental Panel on Climate Change) Guidelines 2006, carbon stock calculation should be measurable, transparent, verifiable and consistent through time. At sub-national level, Java Island especially natural forest ecosystem is often overlooked by REDD+ scientists implying that the data and information on carbon stock of natural forest ecosystem in Java Island is still limited. The research has been conducted in sub montane primary forest in conservation area of Mount Halimun Salak National Park (TNGHS) with the objective to estimate the 5 carbon pools at TNGHS. Twenty seven-plots of 20x20 meters were built in the field. Measurement of forest carbon pools was done for above ground, belowground (root), understorey and necromass at primary forest with high and low canopy density. The research showed that TNGHS has a quite high carbon stock potency as followings: aboveground 139.326 tonC/ha, belowground (root) 39.011 tonC/ha, understorey 1,971 tonC/ha and necromass 5.77 tonC/ha. Average of biomass and stand carbon stock in primary forest of TNGHS were 364.503 ton/ha dan 185.177 tonC/ha, respectively. This study recommends to use allometric equation developed by Chave et al. (2005) to estimate forest stand biomass potency at TNGHS.